Determining the Funding of Post-Employment Benefits: The Role of Salary Expense Ratios, Profitability, Inflation, and Interest Rates - Ardi Tauladan Triatmaja; Intan Kurnia Permatasari (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine the effect of salary expense ratio, profitability, inflation rate, and interest rate on the funding level of post-employment benefit obligations in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach using panel data regression analysis. The research data were obtained from the financial statements of SOEs published on the Indonesia Stock Exchange during the observation period. The results indicate that profitability has a positive and significant effect on the funding level of post-employment benefit obligations. This finding suggests that companies with better financial performance tend to have greater capacity to meet their long-term obligations to employees. Meanwhile, the salary expense ratio, inflation rate, and interest rate do not show a significant effect on the funding level of post-employment benefit obligations. These findings imply that internal corporate factors, particularly profitability, play a more dominant role than macroeconomic factors in determining the funding policy of post-employment benefit obligations. This research contributes to the development of financial accounting literature related to the management of post-employment benefit obligations and provides practical implications for corporate management in designing more effective and sustainable long-term funding strategies.